Development of niosomal nanoparticles loaded with cisplatin and vorinostat combination for cancer therapy - Hazar Ali; Zainab Lafi; Naeem Shalan (PLoS ONE, 2026)
Cisplatin (CIS) remains a cornerstone of chemotherapy but is limited by resistance and systemic toxicity. Combining DNA-damaging agents with epigenetic modulators such as vorinostat (VOR) offers a promising strategy to enhance efficacy. However, the co-delivery of these drugs is challenging due to their distinct physicochemical properties. The aim was to develop and characterize niosomal nanoparticles co-loaded with CIS and VOR (NIO-CIS-VOR) and to assess their physicochemical characteristics and in vitro anticancer activity. Niosomes were prepared using ethanol injection, with CIS entrapped in the aqueous core and VOR in the lipid bilayer. Characterization included particle size, polydispersity index (PDI), and zeta potential by DLS, morphology by TEM, and encapsulation confirmation by FTIR. Encapsulation efficiency (EE%) and drug release were determined by HPLC. Cytotoxicity, caspase-3/7 activation, colony formation, and wound healing assays were conducted in HT-29, A549, and PANC-1 cancer cell lines. Optimized NIO-CIS-VOR nanoparticles exhibited a mean diameter of 152.7 nm, PDI of 0.12, and zeta potential of –9.79 mV, with spherical morphology. Encapsulation efficiency of NIO-CIS-VOR reached 89.3% for CIS and 52.1% for VOR. The formulation showed sustained release over 72 h, with cumulative release of 62% (CIS) and 38% (VOR) at 6 h. Cytotoxicity assays demonstrated markedly reduced IC50 values for NIO-CIS-VOR compared with free drugs: 1.8 µM vs. 4.47 µM (CIS) and 3.4 µM (VOR) in HT-29; 0.95 µM vs. 3.8 µM and 3.1 µM in A549; and 2.37 µM vs. 13.9 µM and 3.66 µM in PANC-1. Enhanced apoptosis and reduced colony formation further confirmed superior anticancer activity.In Conclusion the Co-loaded niosomes achieved efficient co-delivery, sustained release, and synergistic anticancer effects, highlighting NIO-CIS-VOR as a promising nanocarrier for combination cancer therapy.